Positive Solutions for Schrödinger-Poisson Systems with Sign-Changing Potential and Critical Growth. (2nd July 2020) - He, Pengfei; Suo, Hongmin
Abstract : In this paper, we study the existence of positive solutions for Schrödinger-Poisson systems with sign-changing potential and critical growth. By using the analytic techniques and variational method, the existence and multiplicity of positive solutions are obtained.